Redescription of Daphnia turbinata Sars, 1903 (Crustacea: Cladocera: Daphniidae) - Zuykova, Elena I.; Sheveleva, Natalia G.; Kotov, Alexey A. (Zootaxa, 2019)
The genus Daphnia O.F. Müller (Crustacea: Cladocera: Daphniidae) has a long history of its study, it attracts maximum attention of evolutionary biologists as compared to other cladoceran taxa. But still there are many unresolved problems concerning the genus taxonomy. We redescribe forgotten Daphnia (D.) turbinata Sars, 1903 which has a relatively narrow distribution in the Altay-Sayan mountain region (southern Siberia and Mongolia). Diagnostic characters of the taxon are discussed as well as possibilities of morphological discrimination of taxa within the D. (D.) longispina species group.